Morphological Analysis of Nose in Patients of Tessier No. 0 Cleft With a Bifid Nose in China - Wang, Xin; Wang, Huan; You, Jianjun; Zheng, Ruobing; Xu, Yihao; Zhang, Xulong; Guo, Junsheng; Fan, Fei (Frontiers in Pediatrics, 2021)
Objective: Facial cleft involves complex malformations. No study assessed the facial deformity of Tessier No. 0 cleft with a bifid nose. Thus, we used anthropometric measurements to access the nose in patients. Methods: A total of 24 bifid nose deformities underwent surgery at our institution between 2010 and 2019. Standardized photographs were taken preoperatively and postoperatively. Landmarks were identified on these images; measurements for nasal analysis were performed and compared with the established Chinese norms. Surgical method differences were also analyzed. Results: The median follow-up time was 2.51 years. Postoperatively, there is a significant difference in comparison with preoperative in the nasal index, medial canthus and nose width index, nasolabial angle, nasofacial angle, ala length and nasal bridge length index, nasal tip protrusion and nasal width index, and nasal width and ala length index. Furthermore, the medial canthus and nose width index, and nasal width and ala length index were significantly larger in ordinary people, while ala length and nasal bridge length index and nasal tip protrusion and nasal width index were smaller. After surgery, most angles and index were standard except the nasolabial angle in the females, and ala length and nasal bridge length index in the males. Moreover, as for the group of costal cartilage transplantation, most index and angles have improved after surgery including nasolabial angle, nasofacial angle, ala length and nasal bridge length index, nasal tip protrusion and nasal width index, and nasal width and ala length index. However, only nasal tip protrusion and nasal width index, columella length and nasal tip protrusion index, and nasal width and ala length index in the silicone prosthesis group implantation has significance. Costal cartilage transplantation can also better improve ala length and nasal bridge length index than the silicone prosthesis implantation. Conclusion: Most defects can be repaired with surgery, but the outcome has a lack of evaluation. Thus, anthropometric assessment can serve as a material for nasal and reconstructive surgery.